2009
DOI: 10.2190/om.58.3.b
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from the Dead: The Experiences of Undergraduates Working with Cadavers

Abstract: Dissection of a human cadaver is a time-honored tradition for teaching anatomy in medical education. However, in recent years, for a variety of reasons, including costs and ethical concerns, some medical programs have ceased cadaver dissection in exchange for virtual dissection of cadavers in cyberspace. Past research suggests that students find work on a cadaver to be distressing, but also rewarding. This study analyzed journal entries from 21 undergraduate students working with a cadaver in a gross anatomy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 19 publications
2
41
0
1
Order By: Relevance
“…Some studies have reached values between 85.5% and 90% (Izunya et al, 2010;Mompeó Corredera, 2014) for this measure, and others just 15.8% (Dinsmore et al, 2001). The practice is perceived as satisfactory and students recommend it also as a way of learning anatomy (Robbins et al, 2009;Böckers et al, 2010;Bekele et al, 2011;Oyeyipo and Falana, 2012;Karau et al, 2014;Van Wyk and Rennie, 2015) (even in our case where the students have been trained in a digital environment), which is similar to data published elsewhere (Elizondo-Omaña et al, 2005;Azer and Eizenberg, 2007;Leboulanger, 2011;Qamar and Osama, 2014;Estai and Bunt, 2016). Also, up to 60% of the students suggested that the dissections offer a good opportunity to raise awareness and made them consider disease and death in more concrete sense, something that may not have happened had they not gone through this experience (Ellis, 2001;Aziz et al, 2002;Redwood and Townsend, 2011;Mompeó Corredera, 2014;Ghosh, 2017).…”
Section: Dissection Versus Other Learning Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have reached values between 85.5% and 90% (Izunya et al, 2010;Mompeó Corredera, 2014) for this measure, and others just 15.8% (Dinsmore et al, 2001). The practice is perceived as satisfactory and students recommend it also as a way of learning anatomy (Robbins et al, 2009;Böckers et al, 2010;Bekele et al, 2011;Oyeyipo and Falana, 2012;Karau et al, 2014;Van Wyk and Rennie, 2015) (even in our case where the students have been trained in a digital environment), which is similar to data published elsewhere (Elizondo-Omaña et al, 2005;Azer and Eizenberg, 2007;Leboulanger, 2011;Qamar and Osama, 2014;Estai and Bunt, 2016). Also, up to 60% of the students suggested that the dissections offer a good opportunity to raise awareness and made them consider disease and death in more concrete sense, something that may not have happened had they not gone through this experience (Ellis, 2001;Aziz et al, 2002;Redwood and Townsend, 2011;Mompeó Corredera, 2014;Ghosh, 2017).…”
Section: Dissection Versus Other Learning Techniquesmentioning
confidence: 99%
“…In addition to being a useful tool to learn anatomy, it improves the students’ spatial reasoning skills and helps them relate structures to their images as they are usually represented. Dissection also promotes self‐reflection and integration of the cognitive and affective skills required for medical practice (Rizzolo and Stewart, ; Ahmed et al, ), and it is a useful tool to encourage teamwork, professional development and leadership among the students (Pawlina et al, ; Robbins et al, ; Talarico, ; Flack and Nicholson, ). Some have argued it constitutes the foundation of formal anatomy teaching (Rizzolo and Stewart, ; Lee et al, ; Somanath et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…If a student fails to adopt in such a way then he / she may develop symptoms like exhaustion, "burn out," cynicism, impaired empathy in patient-physician relationships, or being unable to deal with the stress of working with live patients (25,26). The first student-cadaver encounter in dissection hall is the "nodal point" -from absolute convergence to comparative divergence [27].The present study is the extended process of our initiative named "cadaver disrobing".…”
Section: Discussionmentioning
confidence: 99%
“…However, in recent years, for a variety of reasons, including costs and ethical concerns, some medical programs have ceased cadaver dissection in exchange for virtual dissection of cadavers in cyberspace 2 . The traditional anatomy education based on topographical structural anatomy taught by didactic lectures and complete dissection of the body with personal tuition has been replaced by a multiple range of special study modules, problem-based workshops, computers, plastic models and many other teaching tools 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Past research suggests that students find work on a cadaver to be distressing, but also rewarding 2 . Hands-on educational experiences on cadavers can also stimulate student interest, increase knowledge retention and enhance development of clinical skills 3 .…”
Section: Introductionmentioning
confidence: 99%